Pengaruh Kejelasan Sasaran Anggaran, Akuntansi Pertanggungjawaban, Dan Latar Belakang Pendidikan Terhadap Kinerja Manajerial Di Satuan Kerja Kementerian Perindustrian Padang - Hayatul Hikmah Johan; Efrizal Syofyan (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to 1) The extent to which the clarity of budget targets influences the management performance in the Work Unit of the Ministry of Industry of Padang. 2) The extent to which responsibility accounting influences managerial performance in the Work Unit of the Ministry of Industry, Padang. 3) The extent to which educational background influences managerial performance in the Work Unit of the Ministry of Industry of Padang and 4) The extent to which clarity of budget targets, responsibility accounting and educational background influences simultaneously on managerial performance in the Work Unit of the Ministry of Industry of Padang. In this study the design of this study is the Design of Causality. The data used are 1) primary, which is the answer to be analyzed for statistical testing purposes, 2) Secondary data, i.e. data needed to support this study were obtained from primary data, ie data obtained directly from the Work Unit of the Ministry of Industry of Padang concerning clarity budget goals, accountability accounting, educational background and managerial performance. This means that together with the variables of the clarity of budget targets, accountability accounting and education affect managerial performance in the Work Unit of the Ministry of Industry, Padang.